Trees Configuration Model for Hot Humid Tropic Urban Parks - Wardoyo, Jono; Budihardjo, Eko; Prianto, Eddy; Nur, Muh (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2011)
Main climatic thermal problems in urban park in hot humid tropic area are how to minimize high solar radiation and to optimize the wind. Trees have potentials in ameliorating urban park microclimate. Trees configuration is one of determining factors to get benefit of vegetation potential in hot humid urban park.Microclimate simulation of 3 (three) different tree configurations in selected urban park model is carried out with three-dimensional numerical model, ENVI-Met V.3.1 which simulates the microclimatic changes within urban environments in a high spatial and temporal resolution. The simulation results show that an east – west orientation tree line configuration model has a higher temperature reduction compared with the base case model.Keywords: Urban park, hot humid tropic, tree configuration model